Aquaporin 12 Is Expressed in the Stomach and Liver of the Spiny Dogfish (Squalus acanthias) - Christopher P. Cutler; Jade Bender; Sarah Conner; Esosa Omoregie (Journal of Marine Science and Engineering)
The sequence of Aquaporin 12 (AQP12) cDNA was amplified from spiny dogfish (Squalus acanthias) cDNAs using degenerate PCR, followed by 5′ and 3′ RACE PCR. The AQP12 nucleotide sequence had an open reading frame of 300 amino acids, which included one or more N-glycosylation sites. Degenerate and tissue PCRs revealed that AQP12 is expressed at the highest levels in the liver, followed by the pyloric stomach and the esophagus/cardiac stomach, with a small amount potentially present in the eye. A polyclonal antibody was made using a peptide from the derived amino acid sequence. Western blotting with the antibody showed faint banding around the size expected (33 kDa) by the 300 amino acid protein. A few more intense bands were seen at around 40 kDa and larger sizes. Immunohistochemistry in cardiac stomach tissue sections showed staining in a few sporadic paneth-like secretory cells along the surface of the epithelium. High-magnification imaging showed that the AQP12 staining was located in the membrane of secretory granules in the apical pole of the cells. This localization is reminiscent of the AQP12 localization in pancreatic acinar cells, where it is found in the membrane of zymogen granules containing digestive enzymes.